Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/ijfs.13530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure on the quality of four edible flowers: Viola × wittrockiana, Centaurea cyanus, Borago officinalis and Camellia japonica

Abstract: SummaryThe aim of the study was to evaluate the effect of high hydrostatic pressure (HHP) on the appearance, bioactivity and microbial content of four edible flowers along storage. Several treatments at 75-450 MPa and holding times (1, 5 and 10 min) were applied. Borage and camellia were unacceptable after all treatments, while centaurea showed good appearance at 100/5 MPa min À1; however, the shelf life did not increase. Pansies treated at 75/5 and 75/10 MPa min À1 also retained the appearance of fresh flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Thus, some water loss was observed, but as the sugar layer was so significant, pansies' appearance was preserved. Furthermore, in a previous study the shelf-life of fresh white pansies was determined and they only maintained good appearance until six days (Fernandes et al, 2017). So, crystallized pansies have a shelf-life 15 times longer than fresh flowers.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, some water loss was observed, but as the sugar layer was so significant, pansies' appearance was preserved. Furthermore, in a previous study the shelf-life of fresh white pansies was determined and they only maintained good appearance until six days (Fernandes et al, 2017). So, crystallized pansies have a shelf-life 15 times longer than fresh flowers.…”
Section: Resultsmentioning
confidence: 98%
“…For example, borage and camellia showed an unacceptable appearance (loss of structure and firmness) after HHP application, while centaurea presented good appearance at 100/5 MPa/min; however, the shelf life did not increase. [37] On contrary, pansies submitted at 75/5 or 75/10 MPa/min maintained good appearance over 20 days of storage at 4°C, as well as HHP induced the production of bioactive compounds. This phenomenon might be associated with structural alteration of the cells provoked by the HHPs, yielding a higher amount of extracted metabolites or a physiological response of the flower to stress conditions at higher pressurization levels.…”
Section: High Hydrostatic Pressurementioning
confidence: 93%
“…This phenomenon might be associated with structural alteration of the cells provoked by the HHPs, yielding a higher amount of extracted metabolites or a physiological response of the flower to stress conditions at higher pressurization levels. [37] The effect of HHP on the retention and bioactivity of natural phytochemicals present in Echinacea purpurea, as well as the microbial load, were studied by Chen et al [38] They reported that HHP significantly reduced the microbial contamination in flowers without affecting the retention of phytochemical, such as chicoric, caftaric and chlorogenic acids, and total alkamides.…”
Section: High Hydrostatic Pressurementioning
confidence: 99%
“…In the last years, new technologies have been applied to extend the shelf‐life and maintain the quality of edible flowers, such as high hydrostatic pressure (HHP) (Fernandes, Casal, Pereira, Ramalhosa, & Saraiva, 2017a), edible coatings (Fernandes, Casal, Pereira, Pereira, et al., 2018; Fernandes, Pereira, et al., 2018), drying (Fernandes, Casal, Pereira, Saraiva, & Ramalhosa, 2018), and irradiation (Koike et al., 2015). In particular, pansies treated with HHP maintained good appearance more 14 days than untreated and induced the production of bioactive compounds (Fernandes et al., 2017a). Concerning edible coatings, pansies increased shelf‐life more 7 days than uncoated, and improved their physicochemical and microbiological quality (Fernandes, Casal, Pereira, Pereira, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%